Tighter control over foreign capital - Rolf Sutter (Intereconomics, 1976)
Foreign investors in Malaysia were greatly disquieted when the Petroleum Development (Amendment) Act, 1975, and the Industrial Coordination Act were passed by the Malaysian Parllament. Both these enactments and the re-formulated Standard Conditions for Foreign Investments are Indicative of the Malaysian Government's desire for tighter control over the national resources and over the foreign enterprises.
Keywords: 330; Malaysia